2022
DOI: 10.1002/edn3.352
|View full text |Cite
|
Sign up to set email alerts
|

Environmental DNA reflects common haplotypic variation

Abstract: CIMA, CH, MK, GJJ, MB, and NJG helped to conceive and design the study. CIMA acquired the data with help from CH and analysed it with the guidance of HC. CIMA wrote the manuscript with input from HRT, MK, MB, NJG, and CH.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…The emergent field of eDNA‐based population genetics could have a great potential to study fish population connectivity across depths (Adams et al, 2019 ). For instance, eDNA has been recently used to investigate diversity within populations of Striped red mullet ( Mullus surmuletus ; e.g., Macé et al, 2022 ), or Blackfoot pāua ( Haliotis iris ; Adams et al, 2022 ), and to successfully estimate population genetic differentiation like for the whale shark (Sigsgaard et al, 2016 ). Only through standard, sustained and multi‐objectives observations at all depths we could get the insights needed to understand the fundamental ecological processes that govern the dynamics of marine ecosystems, and design depth‐specific strategies to effectively protect them in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The emergent field of eDNA‐based population genetics could have a great potential to study fish population connectivity across depths (Adams et al, 2019 ). For instance, eDNA has been recently used to investigate diversity within populations of Striped red mullet ( Mullus surmuletus ; e.g., Macé et al, 2022 ), or Blackfoot pāua ( Haliotis iris ; Adams et al, 2022 ), and to successfully estimate population genetic differentiation like for the whale shark (Sigsgaard et al, 2016 ). Only through standard, sustained and multi‐objectives observations at all depths we could get the insights needed to understand the fundamental ecological processes that govern the dynamics of marine ecosystems, and design depth‐specific strategies to effectively protect them in the future.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that our approach has high sensitivity and accuracy, but a slight risk of false negatives, in return for the least possibility of false positives. We consider that the use of such a stringent denoising approach is essential in evaluating the genetic structure of populations with low nucleotide diversity, where the specious error sequences may easily lead to overestimation of the genetic diversity (Adams et al, 2022; Elbrecht et al, 2018). We also confirmed that our approach is more sensitive than or as sensitive as the traditional sampling‐based approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons between population genetic data obtained from eDNA and traditional tissue sampling can help identify genetic variation that may otherwise be missed in eDNA samples. This was explored by Adams et al (2023) in their study investigating haplotypic variation in Blackfoot Pãua (Haliotis iris), a species of abalone. The authors demonstrate the potential for eDNA sampling to uncover common haplotypic variation but concluded that rare (<5%) haplotypes were seldom recovered.…”
Section: Environmental Dna a S A Source Of P Opul Ati On -Le Vel G En...mentioning
confidence: 99%
“…While some of these limitations are inherent, others may be overcome through technological or methodological improvements. For example, research byAdams et al (2023) andWakimura et al (2023) provides valuable insight into the issues of sensitivity and reliability of population genetic data obtained from eDNA samples and suggests methods for improvement.…”
mentioning
confidence: 99%